TRICHURIS OVIS INFECTION RATES IN THE DRY SEASON IN THE KUPANG POLITANI FIELD LABORATORY - Wirawan, I Gusti Komang Oka; Semang, Agustinus; Aoetpah, Aholiab; ., Suryawati (Buletin Veteriner Udayana, 2023)
The goats being raised semi intensively on the field laboratory of State Agricultural Polytechnic of Kupang were kacang goats ( Capra hircus ). Objective: to measure Trichuris ovis infectious levels based on age during dry season. Nine heads of goats were grouped into two of four for 6 to 7 and five for 18 to 24 month old. Two methods to identify morphological worm eggs are sedimentation and floating; while infectious intensity was using McMaster method. Faecal samples for the two groups were collected twice a week. Descriptive analysis was applied to determine gastrointestinal endoparasites and endoparasite infectious intensity, so that of ambient temperature of pasture. The results showed that average infectious intensity of Trichuris ovis worm eggs for 6 to 7 month old goats was 100 TTG while that for 18 to 24 month old was 200 TTG. It can be concluded that the intensity of Trichuris ovis infection in goats aged 18 to 24 months is higher than that aged 6 to 7 months and is included in the light infection category. This infection category is influenced by season and food source. The difference in the age of the goats is one of the factors causing the difference in the intensity of Trichuris ovis infection between the two groups. The author suggests that in further Res. it would be better to use a larger number of samples with a longer Res. time so that the results are more accurate.